Leading from your best self : develop executive poise, presence, and influence to maximize your potential - Salafia, Rob (McGraw-Hill Professional, 2019)
Through specific techniques, activities, and personal stories, this hands-on guide illustrates how to tap into your own inner resources and experiences, show up with greater self-confidence, and make the shift to more inclusive modes of leading. --